TANTANGAN DAN INOVASI DI ERA PEMBELAJARAN DIGITAL DALAM MENINGKATKAN KUALITAS PENDIDIKAN DI ABAD KE-21 - Adin Hamzah Al Arif; Septi Gumiandari (ENTINAS: Jurnal Pendidikan dan Teknologi Pembelajaran, 2024)
Digital learning has become an important part of education in the 21st century. However, the use of technology in learning also poses challenges and requires innovation to improve the quality of education. One of the main challenges is the technology gap between students and teachers. Not all students have the same access to digital devices and the internet. Therefore, innovation is needed to ensure that all students have equal opportunities to access and utilize digital learning. Apart from that, digital learning also presents new challenges in terms of managing and evaluating learning. Teachers need to develop new skills to manage and monitor online learning, as well as evaluate student progress in an effective way. However, digital learning also has great potential to improve the quality of education. By using technology, teachers can create more interesting and interactive learning experiences. They can utilize a variety of digital resources, such as videos, simulations, and games, to help students understand concepts better. In addition, digital learning also enables collaboration between students and teachers around the world. Through online learning platforms, students can interact and collaborate with students from other countries, which broadens their horizons and develops social skills. In order to face challenges and exploit the potential of digital learning, innovation in education is very important. Teachers need to continue to develop and update their skills in using technology in learning. Apart from that, educational institutions also need to support innovation by providing adequate infrastructure and the necessary training. By overcoming challenges and implementing innovation in digital learning, we can improve the quality of education in the 21st century. This will equip students with relevant skills and knowledge in an increasingly connected and digital world.